Attitudes to Mandarin Chinese varieties in Singapore - Cavallaro, Francesco (2020)
This study aims to shed light on the attitudes of Chinese Singaporeans and Chinese nationals residing in Singapore to varieties of Mandarin Chinese. 64 Singaporean Chinese and Chinese national participants took matched and verbal-guise tests, evaluating recorded speakers of two varieties of Singapore Mandarin (standard and colloquial) and the variety spoken in the PRC on status and solidarity traits. These evaluations were followed by optional questionnaire items intended to probe for additional more insights into the participants' attitudes and perceptions of one another. Both Singaporean Chinese and Chinese national participants assigned higher status to the PRC's variety of Mandarin. Attitudes toward the two varieties of Singapore Mandarin, however, varied, with Singaporeans rating the standard variety higher than the colloquial variety on all traits and Chinese nationals favouring the colloquial variety. Interestingly, for all three varieties of Mandarin, solidarity traits were rated higher than status traits by all participants, suggesting that, in Singapore, Mandarin Chinese is now viewed more as a language of solidarity than status.